Pengaruh Pemberian Bokasi Terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum Frutescens L) - Dewi Rofita (LPPM Politeknik Pratama, 2024)
Cayenne pepper (Capsicum frutescens L) is a type of horticultural plant that has small fruit with a spicy taste. Chili is one of the important vegetables and has high economic value in Indonesia. The solid waste from the tofu industry in the form of tofu dregs has a percentage of around 70%. Solid waste or tofu dregs have a higher protein content compared to liquid waste. Tofu dregs contain many compounds such as Nitrogen (N), Phosphorus (P), Potassium. Tofu dregs can be used as a protein source feed ingredient because they contain quite high crude protein ranging from 18-25%, fat 4.5%, crude fiber 18.21%. It is hoped that this content can play a role in plant growth, by processing it as fertilizer. Research objectives (1) To determine the effect of giving tofu dregs bokasi on the growth of cayenne pepper plants (Capsicum frutescens L) (2) To determine the correct dose of tofu dregs bokasi to increase the production of cayenne pepper plants (Capsicum frutescens L). The method used is a Completely Randomized Design (CRD) with one factor, namely bokasi tofu dregs fertilizer and NPK consisting of 7 treatments and 4 replications of observations to be carried out every 14 DAP, 28 DAP and 42 DAP. The application of bokasi tofu dregs and NPK fertilizer is P0 Without bokasi (control), P1: 200 g/tnm tofu dregs, P2: 250 g/tnm tofu dregs, P3: 300 g/tnm tofu dregs, P4: 200 g/tnm dregs tofu + NPK, P5: 250 g/tnm NPK, P6: 300 g/tnm NPK, P7: NPK. The results of the analysis of variance using the BNJ test with a level of 5% showed that the combination of tofu dregs and NPK (P4) fertilizer had a significant effect on growth in stem diameter, number of branches, and leaf greenness in cayenne pepper plants.